Analysis of the Under-Ice Topography in the Arctic Basin as Recorded by the USS Nautilus during August 1958 - McLaren, Alfred S. (ARCTIC, 1988)
The USS Nautilus (SSN-571) was the first vessel to cross the Arctic Basin via the North Pole in early August 1958. During this expedition almost continuous acoustic under-ice thickness distribution profiles were recorded. This article presents an overall statistical analysis of the under-ice draft measurements obtained during this historic cruise. Geographic areas found to have distinct under-ice-characteristics and ice compositions are identified. Principal findings are: (1) Nautilus recorded an overall mean under-ice draft of 3.68 m across the Arctic Basin; (2) the under-ice topography becomes progressively more severe when proceeding from the Canadian to the Eurasian side of the Arctic Basin; (3) the Canada Basin was observed to contain the most moderate under-ice topography and the greatest number of open water and referent polynyas and leads along the transpolar route taken by Nautilus; (4) Nautilus encountered the most severe under-ice topography of the voyage over the Arctic Mid-Ocean Ridge; and (5) an overall Arctic Basin mean of 2.6% open water/new ice (<30 cm) was encountered during her voyage beneath the sea ice cover of the Arctic Ocean.Key words: sea ice, under-ice thickness distribution, sonar, Canada Basin, Central Arctic, Eurasian Basin, arctic submarine Mots clés: glace de mer, distribution de l’épaisseur de la glace mesurée par dessous, sonar, bassin canadien, centre de l’Arctique, bassin eurasien, sous-marin arctique